CONSTRUCTING NATIONAL IDENTITY: A CRITICAL DISCOURSE ANALYSIS OF INDONESIA'S WORLD CUP ASPIRATIONS IN THE JAKARTA POST - Hafiza Saumi Ramadilla; Halimah Br. Surbakti; Gerardo Ryan Tuah Pratama Purba (Adisam Publisher, 2024)
This study aims to conduct a Critical Discourse Analysis (CDA) of the article